Nanotechnologies and ethics: policies and actions (Paris, 2007)
"What health and environmental issues arise with the use of new materials produced by nanoscale technologies? How might nanoscale devices be controlled, and what concerns attend military and biomedical applications of nanotechnologies? What opportunities might these bring for international cooperation addressing the most pressing needs of developing countries?"